2014
DOI: 10.1016/j.peptides.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

CCK-58 elicits both satiety and satiation in rats while CCK-8 elicits only satiation

Abstract: Reduction of food intake by exogenous cholecystokinin (CCK) has been demonstrated primarily for its short molecular form, CCK-8. Mounting evidence, however, implicates CCK-58 as a major physiologically active CCK form, with different neural and exocrine response profiles than CCK-8. In three studies, we compared meal-pattern effects of intraperitoneal injections CCK-8 vs. CCK-58 in undeprived male Sprague-Dawley rats consuming sweetened condensed milk. In study one, rats (N=10) received CCK-8, CCK-58 (0.45, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Th ere are various forms of CCK with various eff ects on the meal size and the intervals between meals. While CCK 58 and CCK-8 both stimulate satiation, thereby reducing meal size, CCK-58 consistently exerts a satiety eff ect (Overduin et al 2014). Similar results have been reported with CCK-33, which has been found to reduce the food intake by prolonging the inter-meal interval (Washington et al 2011;Lateef et al 2012).…”
Section: Role Of the Gastrointestinal Tract Peptidesmentioning
confidence: 99%
“…Th ere are various forms of CCK with various eff ects on the meal size and the intervals between meals. While CCK 58 and CCK-8 both stimulate satiation, thereby reducing meal size, CCK-58 consistently exerts a satiety eff ect (Overduin et al 2014). Similar results have been reported with CCK-33, which has been found to reduce the food intake by prolonging the inter-meal interval (Washington et al 2011;Lateef et al 2012).…”
Section: Role Of the Gastrointestinal Tract Peptidesmentioning
confidence: 99%
“…The major circulating forms are CCK-8, CCK-22, CCK-33, and CCK-58, all having the same attribute, a C-terminal heptapeptide amide sequence for binding [42][43][44]. Although they have the same attribute, not all forms of CCK show equal bioactivity; for example, both CCK-8 and CCK-58 can reduce meal size after administration, but only CCK-58 increases the intermeal interval time, while CCK-8 reduces this interval, as shown in previous studies [45,46]. CCK performs its action through cholecystokinin-1 (CCK1) receptors and/or cholecystokinin-2 (CCK2) receptors [47].…”
Section: Cholecystokininmentioning
confidence: 52%
“…While the earliest studies utilized natural porcine CCK-33, all more recent studies used synthetic CCK, specifically CCK-8, due to ease of synthesis and inclusion of the minimal fragment with full activity and potency at CCK1R, the carboxyl-terminal heptapeptide-amide. In feeding studies, this peptide has been shown to reproducibly reduce meal size [6], however, its impact on inter-meal interval has been variable, with some studies demonstrating more frequent meals (shortening of inter-meal interval), capable of offsetting the beneficial impact of reduced meal size [23, 24]. It is now appreciated that the dominant form of CCK released into the circulation is a longer form of this hormone with an amino-terminal extension, CCK-58 [25].…”
Section: Ligand-directed Bias In Signalingmentioning
confidence: 99%
“…It is now appreciated that the dominant form of CCK released into the circulation is a longer form of this hormone with an amino-terminal extension, CCK-58 [25]. CCK-58 has been consistently shown to not only reduce meal size, but also extend the inter-meal interval [23, 24]. This provides important reassurance that the “ satiation ” effect of CCK (reduced meal size) is not offset by reduced “satiety” (increased meal frequency).…”
Section: Ligand-directed Bias In Signalingmentioning
confidence: 99%